A Case Report of Intracorneal Detergent Particles Deposits - Shivani Sharma; Vaishali Tomar; Rinky Agarwal; Subhash Dadeya (Delhi Journal of Ophthalmology)
Corneal foreign bodies (FBs) are a significant cause of vision loss and morbidity due to long-term sequelae. The most common culprits are metal; others are glass, vegetative matter, and burns. We report a case of a 50-year-old male patient with multiple FBs embedded in the anterior stroma following blunt injury with detergent particles.